Stuck in the Middle: An Analysis of Economic Growth and the Technological Intensity of Exports - Abdel Halim, Aya (AUC Knowledge Fountain, 2022)
Driven by the persistence of some economies’ lower-middle-income status, also known as the middle-income trap, this research aims to identify the relationship between exports and their growth rates. A Cobb-Douglass model augmented by the different types of exports is employed, and the relationship is estimated for a panel of 77 lower-middle-income economies using multiple two-step system Generalized Method of Moments (GMM) model. This research’s contribution to the literature is two-fold: First, it analyzes exports from both an aggregated level (i.e., total exports) as well as at a disaggregated level by the technological intensity of exports. To add, the panel of lower-middle-income economies is studied as a whole, as well as divided by their trade openness levels, then by their different economic sizes. The findings firstly indicate a lack of homogeneity between countries of the used panel. Exports appear to have a significant relationship with economic growth in countries that are relatively more open or larger. Second, spillover effects were identified in more open economies. To add, the role of capitalizing on factor endowments was pronounced throughout the panel. Evidence of the Dutch Disease effect was also observed. Finally, an additional estimation including imports suggests that growth from imports could be one of the determinants to growth of the panel.